Mrs. Mack - Polacco, Patricia (New York : Puffin Books, 2001)
The author remembers the summer when she was ten years old and staying with her father in Michigan where she took riding lessons and became best friends with a perfect horse. Patricia Polacco presents a true story from her childhood, when she was finally old enough to learn to ride a horse. Her dreams of riding a beautiful steed are dashed when her father takes her to a stable in the rundown section of town. But it's there Patricia meets Mrs. Mack and a mare named Penny, who help her overcome her fears and change her life forever. Full-color illustrations.
004-008.
Keywords: Horses -- Fiction; Michigan -- Fiction